FACTORS THAT INFLUENCE ATTITUDE TOWARDS ONLINE SHOPPING AT SHOPEE AMONG GENERATION Z - Gilberto Kalim; Louis Utama (Graduate Program of Universitas Tarumanagara, 2024)
This research aims to examine the influence of relative advantage and E-WOM on trust and attitude towards online shopping, as well as examining the influence of trust on attitude towards online shopping. Then this research also aims to empirically test trust as a mediator of the relative advantage and E-WOM variables on attitude towards online shopping. The sample in this study was collected using a non-probability sampling technique and using a purposive sampling method. The data in this research was collected using a questionnaire distributed online via Google Form. The total sample in this study was 174 respondents who were Generation z Shopee consumers in Jakarta, had written reviews on Shopee product pages, and had shopped at Shopee at least three times within one month. The data that was collected was then processed using PLS-SEM with the help of SmartPLS version 3 software. The results of this research show that relative advantage and E-WOM have a positive and significant influence on trust. Likewise, the variables relative advantage, E-WOM, and trust have a positive and significant influence on attitude towards online shopping. In addition, the trust variable was found to be able to mediate relative advantage and E-WOM on attitude towards online shopping. The implication of this research is that Shopee understands appropriate actions to encourage positive attitude towards online shopping activities, such asguarantee the quality of its products and services and also Shopee need to be able to guarantee the security of its users data, both personal data and financial data.